Character Transformation Through Music:An Analysis Of The Role Of Music In Character Building Of The Congregation And Music Accompaniment At Gki Solafide Sereh - Ristua, Yohanna; Polhaupessy, Yustinus (JUPE : Jurnal Pendidikan Mandala, 2025)
Church music at GKI Solafide Sereh plays a central role in shaping the character of the congregation and music accompanists. This study aims to analyze the extent to which church music influences spiritual and social character transformation through a qualitative approach. Data were collected through in-depth interviews with congregants and music accompanists, then analyze inductively to explore the meaning of participants' experiences. The results showed that church music is not just an aesthetic element, but also a spiritual medium that strengthens moral values, builds solidarity, and provides inspiration in facing life's challenges. Congregants reported deep emotional and spiritual experiences when participating in worship music. For musical accompanists, the process of learning and serving builds character traits such as discipline, responsibility, and confidence. In conclusion, church music has transformative power in shaping the character of congregants and accompanists, making it an important element in the development of spirituality and morality of the faith community. These findings provide new insights into the relevance of music as a means of character building in the modern era.